Strategi Mobilisasi Politik Tjokorda Gede Agung Melalui Pura Dadia Pada Pemilu 2019 Di Desa Nyanglan - Punia Manuaba, Ida Bagus Nyoman Baskara; Noak, Piers Andreas; Pramana, Gede Indra (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This research 0 aims to find out how the practice of mass political mobilization of Pura  Dadia conducted by political actor Tjokorda Gede Agung in legislative elections in 2019. Furthermore, the research was framed using 0 the 0 theory 0 of 0 Political 0 Mobilization by Stefano Bartolini. The research 0 method 0 used 0 is a descriptive 0 qualitative 0 method 0 using 0 primary 0 data 0 and secondary 0 data, 0 because 0 it 0 describes 0 and 0 describes 0 the 0 form 0 of relationships related to the practice of mass political mobilization of Pura Dadia. . The results of the study are: first, Tjokorda Gede Agung as a political actor formed and established relationships with figures from the Family Group Pura Dadia to be able to enter the scope of Pura Dadia to gain sympathy and support in the election. Second, political actors Tjokorda Gede Agung had previously had social capital to enter the family realm of Pura Dadia through the mother, Tjokorda Istri.